The American Dream at Home and Abroad: Notes on an International Cultural Myth - Burns, Gerald (Journal of English Studies and Comparative Literature, 2007)
Excerpt Most of us in the academe these days, scholars and students alike, know the shortcuts to something to say on a given topic. First, to get the general lay of the land and maybe a few directly relevant sources, we enter a term for a Google search and see what turns up. Then, perhaps to identify a book or two that can bring us straight to the heart of the question, we check out Amazon.com. In the case of the current subject, however, I have found neither of these strategies adequate. Googling “American Dream” returns 64,400,000 hits: one, it would seem, for nearly every articulate person likely to have experience with or an opinion on the matter. Amazon doesn’t offer any clearer path. Fourteen books with the phrase “American Dream” in the title were published in 2005 alone, with more in the pipeline for this year. In short, the starting point for any inquiry into this broadly familiar phenomenon, extending, as my title indicates, beyond the borders of the United States, and as I surmise of special moment here in the Philippines, must lie with definitions and with limitations of focus.